Nursing peer review : a practical, nonpunitive approach to case review - Harrington, Laura Cook; Smith, Marla, MHSA (HCPro, 2015)
Nursing Peer Review, Second Edition, is a comprehensive guide for establishing a formal case-based nursing peer review program, including all the tools and procedures organizations need to build and manage a structure to conduct systematic evaluation of clinical care. The book takes nurse managers through every step of the process: explaining nonpunitive nursing peer review, creating a system, identifying cases, conducting reviews, and taking appropriate action based on the outcomes of the reviews. Nurse leaders are responsible for upholding the ANA Code of Ethics, which concerns issues of accountability for the professional nurse and includes requirements for peer review to ensure high-quality patient care. This book offers them the processes to help do this. It provides a framework for nurses to hold them accountable for their practice, reveal educational gaps, help identify system and process errors, and indicate whether changes in practice are necessary to improve patient outcomes. Inside this book, you will find all the resources you need to get your nursing case-based peer review program up and running, including: - Details of the benefits and rationale of case-based nursing peer review - Easy-to-follow, multi-step system for implementing a case-based peer review program - In-depth content on how to conduct chart reviews - Sample case studies to illustrate the case-based peer review process - Tips on using case-based peer review data to benchmark performance and track and trend peer review results - A comprehensive set of downloadable, customizable tools to create a structured evidence-based case-based peer review process - The formal structure to conduct a systematic evaluation of clinical care.